Combined spatial and retrospective analysis of fluoroalkyl chemicals in fluvial sediments reveal changes in levels and patterns over the last 40 years. (October 2019) - Mourier, B.; Labadie, P.; Desmet, M.; Grosbois, C.; Raux, J.; Debret, M.; Copard, Y.; Pardon, P.; Budzinski, H.; Babut, M.
Abstract: Bed sediments and a dated sediment core were collected upstream and downstream from the city of Lyon (France) to assess the spatial and temporal trends of contamination by per- and polyfluoroalkyl substances (PFASs) in this section of the Rhône River. Upstream from Lyon, concentrations of total PFASs (ΣPFASs) in sediments are low (between 0.19 and 2.6 ng g −1 dry weight - dw), being characterized by a high proportion of perfluorooctane sulfonate (PFOS). Downstream from Lyon, and also from a fluoropolymer manufacturing plant, ΣPFASs concentrations reach 48.7 ng g −1 dw. A gradual decrease of concentrations is reported at the coring site further downstream (38 km). Based on a dated sediment core, the temporal evolution of PFASs is reconstructed from 1984 to 2013. Prior to 1987, ΣPFASs concentrations were low (≤2 ng g −1 dw), increasing to a maximum of 51 ng g −1 dw in the 1990s and then decreasing from 2002 to the present day (∼10 ng g −1 dw). In terms of the PFAS pattern, the proportion of perfluoroalkyl sulfonic acids (PFSAs) has remained stable since the 1980s (∼10%), whereas large variations are reported for carboxylic acids (PFCAs). Long chain- (C > 8) PFCAs characterized by an even number of perfluorinated carbons represent about 74% of the total PFAS load until 2005. However, from 2005 to 2013, the relative contribution of long chain- (C > 8) PFCAs with an odd number of perfluorinated carbons reaches 80%. Such changes in the PFAS pattern likely highlight a major shift in the industrial production process. This spatial and retrospective study provides valuable insights into the long-term contamination patterns of PFAS chemicals in river basins impacted by both urban and industrial activities. Graphical abstract: Image 1 Highlights: Upstream-downstream PFAS concentration gradient in bed sediments in the Rhône River. Reconstruction of temporal trends of PFAS contamination using a sediment core. Evidence of global PFSA background levels. Release of long-chain PFCAs from a point source into the river. Change of PFCA pattern through time likely reflects changes in production processes.